2017
DOI: 10.1080/2162402x.2016.1267892
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cytokine signaling checkpoint CIS activates NK cells to protect from tumor initiation and metastasis

Abstract: The cytokine-induced SH2-containing protein CIS belongs to the suppressor of cytokine signaling (SOCS) protein family. Here, we show the critical role of CIS in suppressing natural killer (NK) cell control of tumor initiation and metastasis. -deficient mice were highly resistant to methylcholanthrene-induced sarcoma formation and protected from lung metastasis of B16F10 melanoma and RM-1 prostate carcinoma cells. In contrast, the growth of primary subcutaneous tumors, including those expressing the foreign ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 27 publications
1
49
1
Order By: Relevance
“…Having shown that we can separate and analyze the effects of IL‐15 on cell proliferation and survival, we were interested in examining how known modifications to the IL‐15 signaling pathway enhance or diminish these parameters. We have previously identified Cish as a critical checkpoint in IL‐15 signaling in NK cells, with Cish ‐null NK cells displaying a hyper‐proliferative and hyper‐functional phenotype . To further delineate the contribution of Cish in NK cell survival and proliferation, Cish −/− and WT NK cells were cultured in IL‐15 concentrations ranging from 0.5 to 100 ng/ml and were routinely analyzed for total cell numbers and CTV fluorescence, to determine half‐lives and division rates.…”
Section: Resultsmentioning
confidence: 99%
“…Having shown that we can separate and analyze the effects of IL‐15 on cell proliferation and survival, we were interested in examining how known modifications to the IL‐15 signaling pathway enhance or diminish these parameters. We have previously identified Cish as a critical checkpoint in IL‐15 signaling in NK cells, with Cish ‐null NK cells displaying a hyper‐proliferative and hyper‐functional phenotype . To further delineate the contribution of Cish in NK cell survival and proliferation, Cish −/− and WT NK cells were cultured in IL‐15 concentrations ranging from 0.5 to 100 ng/ml and were routinely analyzed for total cell numbers and CTV fluorescence, to determine half‐lives and division rates.…”
Section: Resultsmentioning
confidence: 99%
“…Our decision to ablate the CIS immune checkpoint as a therapeutic strategy was partly based on evidence that this protein functions as a critical negative regulator of IL-15 signaling in NK cells. 17,21 Thus, by releasing a potent brake on IL-15 activity, we sought to enhance NK cell activation, expansion and cytotoxic function over extended times. Although this approach is supported by in vitro studies, 17,21 we remained concerned over the possible impact of increased IL-15 signaling on prominent metabolic pathways in NK cells.…”
Section: Resultsmentioning
confidence: 99%
“…17,21 Thus, by releasing a potent brake on IL-15 activity, we sought to enhance NK cell activation, expansion and cytotoxic function over extended times. Although this approach is supported by in vitro studies, 17,21 we remained concerned over the possible impact of increased IL-15 signaling on prominent metabolic pathways in NK cells. In one negative scenario, long-term exposure to IL-15 could suppress rather than boost metabolic rates, leading to NK cell exhaustion.…”
Section: Resultsmentioning
confidence: 99%
“…We next addressed the feasibility to delete the intracellular immunotherapy drug target CIS using Cas9-RNP+gCish. Cish has been published by multiple groups to limit IL-15 and TCR signaling in murine NK and T cells, ultimately dampening anti-tumor responses 7,35,36 . Cish was efficiently deleted in human NK cells (45-80% indels in primary cells; 85-93% indels in NK cell lines) yet the inability to sort on Thus, while primary human T cells can be genetically modified by several approaches including lenti/retrovirus transduction, transient transfection and Cas9-RNP 13,24 , the latter approach is the only viable approach for large-scale genetic modification of primary human NK cells.…”
Section: Discussionmentioning
confidence: 99%